2021
DOI: 10.1098/rsif.2021.0266
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed focused ultrasound can improve the anti-cancer effects of immune checkpoint inhibitors in murine pancreatic cancer

Abstract: Pulsed high-intensity focused ultrasound (pHIFU) uses acoustic pressure to physically disrupt tumours. The aim of this study was to investigate whether pHIFU can be used in combination with immune checkpoint inhibitors (ICIs) to enhance survival of tumour-bearing animals. Murine orthotopic pancreatic KPC tumours were exposed both to a grid of pHIFU lesions (peak negative pressure = 17 MPa, frequency = 1.5 MHz, duty cycle = 1%, 1 pulse s −1 , duration = 25 s) and to anti-CTLA-4/anti-PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Activation of anti-tumor immunity promoted by HIFU can be partially explained by tumor debris "left-over" antigens immunogenicity, which was demonstrated by Zhang et al in the murine hepatocellular carcinoma model [143]. Similar investigations have been conducted with other malignancies, such as melanoma, neuroblastoma, or pancreatic cancer [144][145][146][147][148][149]. Wu et al researched tumor debris immunogenic properties in 23 patients with breast cancer.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 93%
“…Activation of anti-tumor immunity promoted by HIFU can be partially explained by tumor debris "left-over" antigens immunogenicity, which was demonstrated by Zhang et al in the murine hepatocellular carcinoma model [143]. Similar investigations have been conducted with other malignancies, such as melanoma, neuroblastoma, or pancreatic cancer [144][145][146][147][148][149]. Wu et al researched tumor debris immunogenic properties in 23 patients with breast cancer.…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 93%
“…The purpose of this review is to detail the most important advances in ultrasound-induced immunity with a particular focus on the field of pancreatic cancer research. Both "thermal" and "mechanical" focused ultrasound can initiate immune responses in tumours by releasing tumour-associated antigens that lead to T cell-specific responses [108], increased tumour infiltrating lymphocytes (TIL) [109] and antigen-presenting cells (APC) [110] in the tumour microenvironment, activation of dendritic cells (DC) [111], change in the immune contexture of tumours [112], induction of the abscopal effect [108] and reversal of T cell anergy and tolerance [113].…”
Section: Therapeutic Focused Ultrasoundmentioning
confidence: 99%
“…Focused ultrasound could enhance the effects of immunotherapy in pancreatic cancer by destroying cancer cells, releasing tumour-specific antigens, DAMPS, and inducing ICD, thus attracting TIL, activating APC, including DC, and increasing the permeability of pancreatic tumour stroma thus allowing more immune-therapeutics to access the tumours (Table 3). Increased T cytotoxic cells, IFNγ + T cytotoxic cells and the ratio of these cells to T regulatory and MDSC in the tumours [112] The first clinical study to report the immunological effects of HIFU in the pancreas was published in 2002. Increased natural killer cell activity and increases in the abundance of TIL were seen after "thermal" HIFU treatment.…”
Section: The Immunological Effects Of Therapeutic Focused Ultrasound ...mentioning
confidence: 99%
See 1 more Smart Citation
“…More anecdotally, two case studies reported abscopal effects following thermal ablation [ 111 , 112 ]. Preclinical data regarding immune effects in animal models of pancreatic cancer have recently been published [ 100 , 101 , 113 , 114 ]. The interested reader can refer to the detailed comprehensive review of those studies recently provided by Mouratidis and ter Haar [ 115 ].…”
Section: Immunotherapymentioning
confidence: 99%